Profitability and Stock Return: Does Capital Structure Mediating This Association? - Fauji Sanusi (Journal of Applied Business, Taxation and Economics Research, 2023)
This study investigates whether profitability contribute to increase stock returns. Further, current study also examines the mediating role of firm’s capital structure on the relationship. Using 14 companies with 126 firm-years observations from listed manufacturing industry from 2009-2017 and rely on path analysis, this study finds that profitability has a significant positive effect on stock returns, but it has no significant effect on DER. In addition, we also evidence that DER has no significant effect on stock return. Therefore, current study document the importance of profitability to create the best market performance without rely heavily on capital structure. The implication of this study is that it is essential for managers to create a sustainable profitability which has possibility to effect firm performance, as the performance may affect capital market perception through the stock price.